COMBINED TECHNICAL SYSTEM - Bugatekin, Ayse T.; Gurcan, Mehmet; Gural, Yunus (Vinca Inst Nuclear Sci, 2019)
Technical systems are important systems frequently used by applied sciences. Proper operation of technical systems is very important. Therefore, the statistically calculated reliability of a technical system is an important indicator for the system. Technical systems occur in different structures depending on the connection types of the components that constitute the system. The connection diagrams of components can be encountered in a highly complex situation. In such cases, the reliability of the system is difficult to calculate. There is no single method in the literature to calculate the reliability of a technical system. The methods in the literature differ according to the connection types of the systems. In this study, a method and a MATLAB program have been proposed for calculating the reliability of k-out-of-n F systems and consecutive k-out-of-n F systems. The proposed method can also be used for different connections.
Keywords: technical systems; reliability of system; mean time to failure